Synthesis, Characterization, and Thermokinetic Analysis of New Epoxy Sugar Derivative - Selinay Y. Erişkin; Fatma Ç. Telli; Yeliz Yıldırım; Yeşim Salman (Journal of Chemistry)
The synthesis of 5,6-O-isopropylidene-1,2-O-(R)-trichloroethylidene-α-D-glucofuranose (compound 1) and 5,6-O-isopropylidene-1,2-O-(R)-trichloroethylidene-3-O-(2′,3′-epoxypropan-1′-yl)-α-D-glucofuranose (compound 2) was carried out. The synthesized compounds 1 and 2 were characterized by nuclear magnetic resonance (1H-NMR), Fourier transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TG). The FTIR and 1H NMR spectra showed that the epoxy group in compound 2 was attached by means of a nucleophilic substitution reaction. The activation energies for thermal degradation of compounds 1 and 2 were calculated from their TG data by using the Kissinger-Akahira-Sunose (KAS) and Tang methods.